Youth Infomediary Campaign on Climate Smart Agriculture (CSA) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The piloting of the Youth Infomediary Campaign on CSA has been completed. The needed materials for integration into agriculture courses in high schools have been developed. The efficacy of the approached has also been evaluated in 2 published journal papers(https://link.springer.com/article/10.1186/s40064-016-3238-6 & http://ajad.searca.org/read-articles/13-view-article?aid=591).